Minimally invasive surgical treatment on delayed uretero-vaginal fistula - Li, Xinying (BMC Urol, 2018)
OBJECTIVE: To evaluate the procedure of endoscopic surgery for ureterovaginal fistula (UVF) and its clinical efficacy. MATERIALS AND METHODS: A retrospective analysis of 46 patients needing treatment for UVF with endourology technology was conducted (all patients had unilateral ureteric injury, 27 left and 19 right). Transurethral retrograde ureteric stenting or realignment retrograde/antegrade approach stenting was used to treat the fistula, and the relation between treatment and prognosis was analyzed. RESULTS: One case failed, the patient undergoing percutaneous nephrostomy instead. Success was achieved in 45 cases, and urinary leakage was stopped 48 h after surgery. Of the 45 patients operated on, 16 had their double-J stents removed after 3–6 months, and 29 needed replacement every 6–12 months. In a postoperative follow-up of 6–36 months, 10 patients had recurrent stenosis needing ureteroscopic endoureterotomy or reexpansion with a balloon. No other complications occurred. CONCLUSIONS: Endoscopic surgery is an effective technology in the treatment of UVF, with the advantages of being effective, reliable, less invasive, and readily accepted by patients.